PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KEMANDIRIAN DAN PEMAHAMAN KONSEP PESAWAT SEDERHANA KELAS VIII SMPN 1 PAMEKASAN - Wardana, Nur Arifinza Desi; Muhajir; Huda, Nuril (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Model problem based learning (PBL) is a problem-based learning approach in which students adjust their minds to transform existing thoughts on topics of interest into rational learning exercises. The aim of this research is to determine the effect of learning models Problem Based Learning (PBL) towards learning independence and understanding concepts. This research is quantitative research and uses Quasi Experimental Design (Quasi-Experiment). This research was conducted from 5 to 9 August 2024, involving 64 class VIII students consisting of 32 class VIIIA students as the control class and 32 class VIIIB students as the experimental class at SMP Negeri 1 Pamekasan on simple airplane material. The research results show that the learning model problem based learning (PBL) can increase the learning independence of the experimental class higher (the average is 77.00) than the control class which is taught using conventional learning (the average is 71.41) and the understanding of the concepts of the experimental class higher (average of 87.41) than the control class (average of 79.63). This is because of the model PBL has the advantage of making the learning of this concept more concrete and directly related to everyday life, thereby helping students learn more actively and easily understand the material better.